If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -3m = 2 Combine like terms: 4m + -3m = 1m 1m = 2 Solving 1m = 2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '1'. m = 2 Simplifying m = 2
| g(x)=36 | | 8-2x-3x=-16-8x | | 2(x+2)=5x-3 | | -6(3z-7)=33 | | 36-(3x+4)=2(x+4)+x | | x-5x+4x-7x= | | x^3-5x^2+2x=-1 | | 3+2k=17 | | x=7ln(y^2-48) | | 2w^2+7w=0 | | 7x=19(2x-7) | | -2x-x+1=0 | | 0.2x^5-2x^3+1.8x+5=0 | | 7+12p=-5 | | -2x-6=2-4-(x-1) | | 0.2x^5-2x^3+1.8x+2=0 | | R^2+10r-30=0 | | 3a+23=53 | | 4x^3+22x^2+24x=0 | | 2x^2-sinx+1=0 | | 16x^2-54x-16=0 | | 1-6x-3x=-17 | | (15)(13)+(15)(7)= | | 2a-18=34 | | 2x-sinx+1=0 | | 8n+2+5n=19 | | 4y+10=x | | 2x=-2-y | | 13=x(4-x) | | 45+0.25m=70+0.15m | | 2f+18=14 | | 2x+y-2z=14 |